Clinical application and outcome of Tenon’s patch graft: A comprehensive review - Rakhi Kusumesh; Alisha Kishore; Anitha Venugopal; Sushmita G Shah; Murugesan Vanathi (Indian Journal of Ophthalmology)
Corneal perforations are potentially sight-threatening conditions if not promptly treated. Management depends on the size, location, cause, and severity of the perforation. Various methods, including tissue adhesives, amniotic membrane grafting (AMG), and keratoplasty, are available. However, the limited availability of donor tissue in emergencies poses a significant challenge. Recently, Tenon’s patch grafting (TPG) has emerged as a promising treatment option due to its autologous nature, availability, and lack of immunogenicity. This review provides a comprehensive overview of various aspects of TPG, along with relevant images. A literature search using keywords such as “Tenon’s patch graft,” “Tenon’s capsule,” “corneal patch graft,” “amniotic membrane,” and “corneal perforations” yielded 37 articles, included in this review. TPG is suitable for cases involving corneal tissue degradation leading to perforation, impending perforation, or descemetocele, with lesion sizes ranging from 2 to 6 mm. For larger perforations, the procedure may be modified by combining it with AMG or tissue adhesives. Postoperatively, the graft undergoes characteristic changes, including epithelialization and collagen deposition, resulting in the formation of a thick scar. Complications such as delayed epithelialization, wound leaks, and graft dehiscence can occur. High success rates have been reported, ranging from 74% to 87%. However, TPG may result in suboptimal visual outcomes, particularly when the graft is centrally located, necessitating future keratoplasty for visual rehabilitation. Overall, TPG is a safe and cost-effective technique for restoring structural integrity in corneal thinning disorders and perforations, especially in emergency settings when donor tissue is unavailable.